ENGINEERING DESIGN OF THE OFF ROAD CAR FORTRESS BUMPER FOR THE HAULING MACHINE MOUNTING (Perner's Contacts, 2016)
The first part of this article deals with the legislative about fortress accessory for mounting on off-road vehicles. In the next part the engineering design of the rear fortress bumper is introduced. It will be equipped with hauling machine and mounted on the Nissan Patrol vehicle so that all essential legislative requirements will be fulfilled. The car modification and also change. These requirements are related to the car modification and also replacement of particular parts.
Keywords: fortress bumper; engineering design; off-road car